2019
DOI: 10.1155/2019/4236562
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Function and Cytokine Production of Natural Killer Cells and Natural Killer T-Like Cells in Systemic Lupus Erythematosis Regulation with Interleukin-15

Abstract: Natural killer cells and NKT-like cells are the first line immune defense against tumor and virus infection. Deficient NK and NKT-like cell effector function may contribute to increased susceptibility to infection in SLE patients. We sought to examine the perforin and granzyme B expression, interferon-gamma (IFN-γ), and tumor-necrosis factor-alpha (TNF-α) production and CD107a degranulation of NK and NKT-like cells from SLE patients and their regulation by IL-15. We established that (1) perforin expression on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…We found that iNKT cells in SLE patients were deficient in number and showed poor response to α-GalCer stimulation, in agreement with previous studies [ 23 , 26 ]. We and others have previous shown the ability of IL-15 to regulate the phenotype and function of NK and NK T-like -cells in SLE patients [ 15 , 27 , 28 ]. Although IL-15 alone did not increase iNKT cell percentage in MNCs, it expanded the absolute counts of iNKT cells, and thus increased cell recovery.…”
Section: Discussionmentioning
confidence: 99%
“…We found that iNKT cells in SLE patients were deficient in number and showed poor response to α-GalCer stimulation, in agreement with previous studies [ 23 , 26 ]. We and others have previous shown the ability of IL-15 to regulate the phenotype and function of NK and NK T-like -cells in SLE patients [ 15 , 27 , 28 ]. Although IL-15 alone did not increase iNKT cell percentage in MNCs, it expanded the absolute counts of iNKT cells, and thus increased cell recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was shown in the same study that the status of decreased CD56 dim NK cells was activated and their IFN- γ levels were increased. Granzyme B + CD56 bright cell ratios were found to be higher in active phase compared to in inactive phase of SLE and those in healthy individuals ( 252 ). In addition, TNF-α levels of CD56 dim NK cells but not CD56 bright NK cells from active SLE patients were demonstrated to be lower than inactive SLE patients and healthy individuals.…”
Section: Natural Killer Maturation Phenotypes Distribution and Funcmentioning
confidence: 99%
“…A recent study showed that CD56 bright NK cells may contribute to SLE development. Serum IL-15 level was elevated in SLE patients, particularly those with active disease (55,56); and an increased number of peripheral blood Ki67 + CD56 bright NK cells was strongly correlated with elevated serum IL-15, clinical severity, and active nephritis in SLE patients (57). The high serum IL-15 level in SLE may be attributable to type I IFN-mediated DC activation; moreover, IL-15 induces the expression of Ki67 in NK cells, which stimulates NK cell proliferation and contributes to pathogenesis of SLE.…”
Section: Nk Cells and Autoimmune Diseases Nk Cells And Systemic Autoimentioning
confidence: 99%